Low Sex Ratio in Children of Professional Basketball Players in Spain - Reyes Palomares, Arturo; Lendínez-Ramírez, Ana María; Ruiz-Galdón, Maximiliano; Reyes-Engel, Armando (Wiley, 2012)
The aim of this study was to ascertain the variations in the reproductive sex ratio (number of men to number of women) among male professional basketball players in Spain. This retrospective, cross-sectional study is based on a survey conducted in the Spanish professional basketball leagues during the season 2009–2010. A total of 172 professional basketball players completed an anonymous survey. Forty-seven of the respondents had offspring, with a total of 61 children: 70% girls and 30% boys, with a sex ratio value of 0.42. Thirty-three basketball players were Caucasian (CAU), with 44 children, nine boys and 35 girls (sex ratio = 0.26). Fourteen were black, of African heritage (AFR), with 17 children, nine boys and eight girls, (sex ratio = 1.12). Differences (P < 0.01) were found in offspring sex ratio values for all basketball players (sex ratio = 0.42) and for CAU group (sex ratio = 0.26) when compared with the general Spanish population (sex ratio = 1.06). Moreover, a significant seasonal variation was observed in CAU offspring sex ratio during the first quarter compared with the rest of the year (0.66 versus 0.12) (P < 0.03). In conclusion, a significant increase in the sex ratio value in favour of female offspring was observed in the group of CAU professional basketball players.
Keywords: Sexo - Determinación - Modelos matemáticos; Deportes; Sex ratio; Basketball players